Multi-functional MnO2 nanomaterials for photo-activated applications by a plasma-assisted fabrication route. Issue 1 (10th October 2018) - Barreca, Davide; Gri, Filippo; Gasparotto, Alberto; Carraro, Giorgio; Bigiani, Lorenzo; Altantzis, Thomas; Žener, Boštjan; Lavrenčič Štangar, Urška; Alessi, Bruno; Padmanaban, Dilli Babu; Mariotti, Davide; Maccato, Chiara
Abstract : F-doped β-MnO2 nanomaterials fabricated using a one-step plasma-assisted route display attractive functional performances in view of photo-activated self-cleaning/antifogging applications and wastewater treatment. Abstract : Supported MnO2 -based nanomaterials were fabricated on fluorine-doped tin oxide substrates using plasma enhanced-chemical vapor deposition (PE-CVD) between 100 °C and 400 °C, starting from a fluorinated Mn(ii ) diamine diketonate precursor. Growth experiments yielded β-MnO2 with a hierarchical morphology tuneable from dendritic structures to quasi-1D nanosystems as a function of growth temperature, whose variation also enabled a concomitant tailoring of the system fluorine content, and of the optical absorption and band gap. Preliminary photocatalytic tests were aimed at the investigation of photoinduced hydrophilic (PH) and solid phase photocatalytic (PC) performances of the present nanomaterials, as well as at the photodegradation of Plasmocorinth B azo-dye aqueous solutions. The obtained findings highlighted an attractive system photoactivity even under visible light, finely tailored by fluorine content, morphological organization and optical properties of the prepared nanostructures. The results indicate that the synthesized MnO2 nanosystems have potential applications as advanced smart materials for anti-fogging/self-cleaning end uses and water purification.